APAKAH ROTATION OF MEDICATION MASIH DIPERLUKAN? - Siti Mardewi Soerono Akbar (Faculty of Dentistry, Universitas Indonesia, 2015)
The endodontic diseases caused by the endodontic flora, exposed to the root canal system. The number of microorganisms detected in an endodontic infection increased to a range of 3 to 12 organisms per infected root canal associated with an apical lesion, the number of colony forming units (CFUs) is usually between 102 and 108. Therefore the endodontic infections are polymicrobial. Rotation of medication is an endodontic prosedur to prevent bacteria from acquiring resistance to the prolonged use of the same disinfectant. The principles of modern endodontic concept of cleaning root canals are: remove microorganisms and pulp debris from the root canal system. Sodium hypochlorite solution, 1.31-2.62% is used for root canal irrigant. If the root canal treatment could not be finished in one visit, calcium hydroxide paste is the recommended for root canal medicament. Because it has been shown as a safely disinfect of the root canal system. The relatively pH value of Calcium hydroxid 13.1, was kept constant for a period of 30 days, induce the apical healing. Eugenol, ChKM, and Ledermix paste can destroy the anaerob bacteria from the infected root canal and irritate the periapical tissue, but Ledermix paste has the toxic selective action to the periapical tissue. Conclusion: the accumulation effect of the root canal dressing using on rotation method, causes toxic effect, so the method is not recommended.